Measurement of dijet production in diffractive deep-inelastic scattering with a leading proton at HERA - Aaron, Francisc Dionisie; Hennekemper, Eva; Krüger, Katja; Lendermann, Victor; Pirumov, Hayk; Sauter, Michel David; Schöning, André; Schultz-Coulon, Hans-Christian (The European physical journal. C, Particles and fields, 2012)
The cross section of diffractive deep-inelastic scattering ep→eXp is measured, where the system X contains at least two jets and the leading final state proton is detected in the H1 Forward Proton Spectrometer. The measurement is performed for fractional proton longitudinal momentum loss x ℙ<0.1 and covers the range 0.1<|t|<0.7 GeV2 in squared four-momentum transfer at the proton vertex and 4<Q 2<110 GeV2 in photon virtuality. The differential cross sections extrapolated to |t|<1 GeV2 are in agreement with next-to-leading order QCD predictions based on diffractive parton distribution functions extracted from measurements of inclusive and dijet cross sections in diffractive deep-inelastic scattering. The data are also compared with leading order Monte Carlo models.
Gesehen am 08.11.2018